The Pressure to paint : Georg Baselitz - Jean Michel Basquiat - Sandro Chia - Francesco Clemente - Enzo Cucchi - Martin Disler - Rainer Fetting - Keith Haring - Jörg Immendorff - Anselm Kiefer - Per Kirkeby - Markus Lüpertz - Michael McClard - A.R. Penck - David Salle - Julian Schnabel - Robin Winters - Cortez, Diego (New York : Marlborough Gallery Inc., 1982)
Georg Baselitz - Jean Michel Basquiat - Sandro Chia - Francesco Clemente - Enzo Cucchi - Martin Disler - Rainer Fetting - Keith Haring - Jörg Immendorff - Anselm Kiefer - Per Kirkeby - Markus Lüpertz - Michael McClard - A.R. Penck - David Salle - Julian Schnabel - Robin Winters
The Pressure to paint, Marlborough Gallery Inc., New York, June 4 - July 9, 1982
boek